Consumer Legal Protection in E-Commerce Transactions: Consumer Protection Law Perspective - Harahap, Syukri Aman; Hakim, Nur; Fitrian, Achmad (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
In the digital era marked by rapid advancements in information and communication technology, e-commerce transactions have become increasingly common, transforming traditional trading methods. This article discusses consumer legal protection in e-commerce transactions from the perspective of the Consumer Protection Act in Indonesia. Although e-commerce offers convenience and efficiency, consumers often face risks such as product discrepancies, delivery delays, and payment security issues. This research employs a normative juridical method with secondary data collection through literature studies. The findings indicate that despite laws designed to protect consumers, suboptimal implementation and a lack of consumer awareness about their rights exacerbate the situation. Effective legal protection requires collective efforts from the government, businesses, and consumers to enhance awareness and compliance with existing regulations.